PCR- and Ligation-Mediated Synthesis of Split-Marker Cassettes with Long Flanking Homology Regions for Gene Disruption in Candida albicans. (June 2000) - de Hoogt, Ronald; Luyten, Walter H.M.L.; Contreras, Roland; De Backer, Marianne D.
Because Candida albicans is a diploid organism, two consecutive steps of gene disruption are required to generate a gene knock-out. The same marker ( URA3 ) is often used for disruption of both copies of the gene. This is possible because, after the first round of disruption, homologous recombination between direct repeats flanking the URA3 marker and the subsequent counterselection allow for the efficient recovery of Ura - revertants. Unfortunately, the URA-blaster disruption cassette cannot be used in a PCR-based disruption approach. The hisG repeats flanking the URA3 gene in the disruption cassette anneal to one another during PCR and thereby prevent amplification of the complete cassette. We explored the use of transformation based on splitmarker recombination to circumvent this problem. To avoid any cloning steps and to retain the advantage of long flanking regions for disruption, we combined this with a PCR- and ligation-mediated approach for generating marker cassettes. We used this approach to disrupt the C. albicans FAL1 (ATP-dependent RNA helicase) gene. Long 5′ and 3′FAL1-specific regions were amplified by PCR and individually ligated to a URA-blaster cassette. The resulting ligation reactions were used separately as templates to generate two FAL1 disruption cassettes with overlapping URA3 marker regions. Simultaneous transformation with both overlapping disruption cassettes yielded efficient disruption of one FAL1 allele.